MKK3- and MKK6-regulated gene expression is mediated by the p38 mitogen-activated protein kinase signal transduction pathway. - Raingeaud, J (1996)
The p38 mitogen-activated protein (MAP) kinase signal transduction pathway is activated by proinflammatory cytokines and environmental stress. The detection of p38 MAP kinase in the nucleus of activated cells suggests that p38 MAP kinase can mediate signaling to the nucleus. To test this hypothesis, we constructed expression vectors for activated MKK3 and MKK6, two MAP kinase kinases that phosphorylate and activate p38 MAP kinase. Expression of activated MKK3 and MKK6 in cultured cells caused a selective increase in p38 MAP kinase activity. Cotransfection experiments demonstrated that p38 MAP kinase activation causes increased reporter gene expression mediated by the transcription factors ATF2 and Elk-1. These data demonstrate that the nucleus is one target of the p38 MAP kinase signal transduction pathway.